Predictive value of the hemispheric infarct hemorrhagic transformation - Mykhailenko, N.; Kuznietsov, A. A.; Kozyolkin, O.; Кузнєцов, Антон Анатолійович; Козьолкін, Олександр Анатолійович (Запорізький державний медичний університет, 2018)
The purpose was to verify the predictive value of the hemispheric infarct hemorrhagic transformation subtype according to the ECASS-II classification. Materials and methods. The analysis of the results of a comprehensive study of 67 patients (24 men and 43 women, mean age 72,1±1.0 years) with hemispheric infarct hemorrhagic transformation was performed, which included a clinical neurological examination using National Institute of Health Stroke Scale assessment upon admission, modified Rankin scale on the 14th day. Hemispheric infarct hemorrhagic transformation subtype was verified on the basis of computed tomography of the brain according to European Co-operative Acute Stroke Study-II classification.
Keywords: тези доповідей